Early NCCT imaging signs for prognostication in intracerebral hemorrhage: a retrospective cohort study with long follow up results - Rong Deng; Chuyue Wu; Lina Zhang; Jing Wang; Jing Guo; Zhenjie Yang; Lei He; Shengli Chen (BMC Neurology, 2025)
Abstract Objective This study intends to investigate the connection between non-contrast computed tomography (NCCT) imaging findings and neurological function scores in patients with intracerebral hemorrhage (ICH) in a long follow up of 451 patients. Methods Between January 2020 and October 2021, a retrospective review was undertaken on patients with ICH. The NCCT imaging results within 24 h of symptom onset, clinical information, biochemical markers and the one-year outcome post-discharge were collected and analyzed. Subsequently, a prognostic model was devised to predict poor outcomes. Results A cohort of 451 patients diagnosed with ICH was analyzed in this study. Adverse prognostic outcomes at three months were found to be independently associated with several factors, including the presence of the swirl sign (P = 0.010), advanced age (P = 0.003), post-ICH modified Rankin Scale (mRS) score (P = 0.003,), time elapsed from symptom onset to NCCT scan (P = 0.018), and the presence of ventricular hemorrhage (P = 0.003). Unfavorable prognosis at 12 months was independently associated with the presence of the island sign (P = 0.001), older age (P = 0.003), post-ICH mRS score (P = 0.003), and HE (P = 0.014). Additionally, the integration of NCCT imaging signs into the predictive model significantly improved its accuracy in predicting adverse outcomes at both three months (AUC = 0.817 vs. 0.782 in the model without NCCT, NRI = 0.219, P = 0.033, IDI = 0.080, P = 0.006) and 12 months (AUC = 0.829 vs. 0.797 in the model without NCCT, NRI = 0.235, P = 0.028, IDI = 0.096, P = 0.003). Conclusions The early imaging features of patients suffering from ICH can provide a more precise prognosis from the analysis of the 12-month follow up results.